Correlated Morphological and Genetic Patterns in Embothrium coccineum (Proteaceae) Across Climate and Geography: Can Embothrium Survive Patagonian Climate Change? - Souto, Cintia Paola (2013)
Adaptive radiation and reproductive isolation can determine the biogeographic structure of any species. We examine patterns of biotic variation in Embothrium coccineum, a Proteaceae tree that spans 20º of latitude and is both morphologically and genetically highly variable. We aim to: (1) explore the correspondence between these biotic patterns and current geographic and climatic gradients, and (2) determine whether and how those patterns are likely to respond to changing climate. We conducted separate Principal Components Analysis on biotic and abiotic sets of variables for 34 populations of Embothrium coccineum, accounting for a large fraction of the total variation in each. We then used canonical correlation analyses to optimize the match of those gradients onto each other. Smaller, rounder leaves and particular alleles typify the colder-drier parts of the range, while larger, lanceolate leaves and other alleles typify warmer-moister areas. Finally we mapped biotic profiles onto a predicted climatic landscape, based on doubling of CO2 projections. The climatic regime is predicted to shift geographically, but this lineage has successfully responded to repeated and dramatic climatic shifts since the Oligocene, and it should also be able to move and adapt quickly enough to meet the present challenge. More generally, our analytic approach can be extended to analysis of biotic and abiotic patterns in other species facing climatic challenges. Where there is enough biogeographic variation to provide adaptively relevant substrate, and where propagule dispersal is sufficiently extensive to keep up with the pace of spatial climatic shift, such taxa should be able to cope with shifting climate.